Injuries of the retrohepatic inferior vena cava and the liver - Koprivica Radenko; Cvijović Radiša; Koprivica Ranka; Smiljanić Radmila (Vojnosanitetski Pregled)
Beckground. Injuries of the retrohepatic inferior vena cava, and the liver have mortality rate up to 71-78%. We presented a patient with combined injury of the retrohepatic inferior vena cava, liver, craniocerebral and thoracic traumas, inflicted in a traffic accident. Case report. Man, 20 years old has been injured in a traffic accident. At admission, 20 minutes after the injury, the patient was comatose and hypotensive. Bloody content was obtained by abdominal tracer. The patient underwent emergent laparotomy, utilizing trifurcated incision and cell saver device. Abdominal exploration revealed two liters of free blood and massive retroperitoneal hematoma. Manual compression of the liver was done, as well as perihepatic packing, complete hepatic vascular exclusion and mobilization of the right liver lobe. Due to impressive chemodynamic instability supraceliac aortic clamping was performed. Upon exposure of the retrohepatic inferior vena cava and right liver lobe, multiple lacerations of retrohepatic inferior vena cava and right hepatic vein, and right hepatic vein avulsion were found. We also identified an injury of VII and VIII segments of the liver (grade V according to the Moore's classification). Nonexpansive hepatoduodenal ligament hematoma and the injury of II and III segments of the liver group II/III according to Moore were found. Venorrhaphy of the inferior vena cava was done in the area of circumference of the right hepatic vein, a portion of which served as autologous vein patch. Continuous prolene 3/0 venorrhaphy of the distal caval laceration was done. Total caval and aorta clamping time of the inferior vena cava was 41 minutes. Atypical resection, debridment, of hepatic segments was done by using a harmonic scalpel. Hepatoduodenal ligament was declamped after 65 minutes. Fibrin glue was applied on the resectioned area of liver. The patient received 3.2 l of autologuos blood transfusion with 5 units of packed red blood cells, 6 units of fresh frozen plasma, 13 units of concentrated thrombocytes and 15 units of cryoprecipitates. Due to coagulopathy, factor rVIIa was administered. Bilateral toracal drainage was done. Small bilateral contusions of the frontal part of the brain were noticed but the patient successfully recovered and was dismissed after three weeks. Conclusion. Combined injuries of the inferior vena cava and the liver befall into the most complex vascular traumas, thus representing a challenge for any complete medical team to manage them. The patient presented in our study was urgently transported to the hospital, immediately operated on applying modern doctrines of anesthesiology, transfusiology and vascular surgery that, all together, resulted into favorable treatment outcome with no distant complications.